2011
DOI: 10.1111/j.2042-3306.2010.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of gastric balloon manometry for estimation of intra‐abdominal pressure in horses

Abstract: Our results suggest that the indirect method used in human patients for estimating IAP by P(ga) is not applicable for horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Ventral abdominocentesis is commonly performed as part of the evaluation of acute abdominal disease in horses, and may offer a practical and easy method to determine IAP in the clinical setting. Further investigation evaluating ventral IAP in horses with abdominal disease (eg, colic, hydrops allantois/amnion) is required to determine the diagnostic value of ventral IAP measurements in clinical decision making as has been suggested by previous investigators …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventral abdominocentesis is commonly performed as part of the evaluation of acute abdominal disease in horses, and may offer a practical and easy method to determine IAP in the clinical setting. Further investigation evaluating ventral IAP in horses with abdominal disease (eg, colic, hydrops allantois/amnion) is required to determine the diagnostic value of ventral IAP measurements in clinical decision making as has been suggested by previous investigators …”
Section: Discussionmentioning
confidence: 99%
“…Intravesicular pressure as an indirect measure and minimally invasive technique for IAP determination is considered the technique of choice over direct intraperitoneal cannulation . Several studies have reported poor correlation between indirect IAP (intravesicular and intragastric) and direct IAP measured in standing horses. High intra‐ and interindividual variability observed with indirect techniques makes direct abdominal cannulation the preferred method of IAP assessment in horses …”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the descriptions for IBP measurement, both air‐filled (Slocombe et al . 1991; Canola et al . 2011b) and fluid‐fluid (Munsterman and Hanson 2011) systems have been used for the purpose of assessment of IAP using IGP in horses.…”
Section: Clinical Measurement Of Iapmentioning
confidence: 99%
“…2011b) and fluid‐fluid (Munsterman and Hanson 2011) systems have been used for the purpose of assessment of IAP using IGP in horses. Gastric balloon distention volumes ranging from deflated balloon (zero) up to 100 ml of infused air, following catheter placement in an emptied stomach (air‐filled system) (Canola et al . 2011b), and from a deflated stomach up to 3000 ml of fluid for gastric distention (fluid‐filled system) (Munsterman and Hanson 2011) have been described.…”
Section: Clinical Measurement Of Iapmentioning
confidence: 99%
See 1 more Smart Citation